Is Nestlé a Lady? The Feminine Brand Name Advantage. (November 2021) - Pogacar, Ruth; Angle, Justin; Lowrey, Tina M.; Shrum, L. J.; Kardes, Frank R.
A brand name's linguistic characteristics convey brand qualities independent of the name's denotative meaning. For instance, name length, sounds, and stress can signal masculine or feminine associations. This research examines the effects of such gender associations on three important brand outcomes: attitudes, choice, and performance. Across six studies, using both observational analyses of real brands and experimental manipulations of invented brands, the authors show that linguistically feminine names increase perceived warmth, which improves brand outcomes. Feminine brand names enhance attitudes and choice share—both hypothetically and consequentially—and are associated with better brand performance. The authors establish boundary conditions, showing that the feminine brand name advantage is attenuated when the typical user is male and when products are utilitarian.